DUAL LOADED LIPOSOMAL PHARMACEUTICAL FORMULATIONS - CHEN GUOQIANG; ZHU DE-MIN (2018)
A pharmaceutical composition can include a plurality of liposomes comprising docetaxel and doxorubicin. In various embodiments, a liposome can include (i) an active pharmaceutical ingredient (API) comprising docetaxel and doxorubicin; (ii) a lipid layer comprising an unsaturated phospholipid, a cholesterol, a cationic lipid, and preferably a pegylated phospholipid; and (iii) an aqueous interior, wherein the docetaxel is in the lipid layer and the doxorubicin is crystallized in the aqueous interior. The liposomes can be used to treat a subject, for example, a human subject having cancer. The cancer can be, for example, a lung cancer, preferably non-small cell lung cancer (NSCLC), colon cancer, breast cancer, or liver cancer. 药物组合物可包含含有多西紫杉醇和多柔比星的多个脂质体。在各种实施方案中，脂质体可包含(i)活性药物成分(API)，其包含多西紫杉醇和多柔比星；(ii)脂质层，其包含不饱和磷脂、胆固醇、阳离子脂质和优选地聚乙二醇化磷脂；和(iii)内部水性部分，其中多西紫杉醇在脂质层中且多柔比星在内部水性部分中结晶。该脂质体可用于治疗受试者，例如患有癌症的人类受试者。癌症可以是例如肺癌，优选非小细胞肺癌(NSCLC)；结肠癌；乳腺癌；或肝癌。